2014
DOI: 10.1007/s10096-014-2240-6
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and susceptibility profile to fluconazole, voriconazole and MXP-4509 of 551 clinical yeast isolates from a Romanian multi-centre study

Abstract: This is the first multi-centre study regarding yeast infections in Romania. The aim was to determine the aetiological spectrum and susceptibility pattern to fluconazole, voriconazole and the novel compound MXP-4509. The 551 isolates were identified using routine laboratory methods, matrix-assisted laser desorption ionisation time-of-flight mass spectrometry (MALDI-TOF MS) and DNA sequence analysis. Susceptibility testing was performed using the European Committee for Antimicrobial Susceptibility Testing (EUCAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
3
13
0
Order By: Relevance
“…These rates are comparable with those from previously published epidemiological studies, but with notable differences (8)(9)(10)(11)(12). Higher rates of resistance for C. tropicalis to voriconazole (25 to 67%) and of different Candida species to posaconazole (18 to 80%) were previously reported using smaller collections of bloodstream isolates (n Ͻ60) and a lower breakpoint of 0.06 mg/liter for posaconazole compared with that in the present study (8,9,11).…”
supporting
confidence: 90%
“…These rates are comparable with those from previously published epidemiological studies, but with notable differences (8)(9)(10)(11)(12). Higher rates of resistance for C. tropicalis to voriconazole (25 to 67%) and of different Candida species to posaconazole (18 to 80%) were previously reported using smaller collections of bloodstream isolates (n Ͻ60) and a lower breakpoint of 0.06 mg/liter for posaconazole compared with that in the present study (8,9,11).…”
supporting
confidence: 90%
“…In accordance with recent studies, using antifungal susceptibility tests that are considered gold standards (CLSI and EUCAST- European committee on Antimicrobial Susceptibility Testing, microbroth assays), the rates of fluconazole resistance in blood stream C. parapsilosis isolates ranges from 3.4 to 7.5 % in the USA [17, 25, 26], 0 to 6.3 % in Europe and up to 5.4 in Asia [17, 27, 28]. …”
Section: Discussionsupporting
confidence: 56%
“…Although there is a general consensus worldwide that C. tropicalis strains exhibit a moderate level of azole resistance (Kothavade et al, 2010; Jiang et al, 2013; Guinea et al, 2014), it is important to note that the rates of C. tropicalis resistance to azoles in North America and most European countries are low. For example, C. tropicalis resistant rates to fluconazole in the United States are generally <7% (Lockhart et al, 2012; Pfaller et al, 2015), whilst those reported in European countries vary from 0 to 12% (Orasch et al, 2014; Minea et al, 2015; Posteraro et al, 2015; Tadec et al, 2016). …”
Section: Discussionmentioning
confidence: 99%